Analisa Qos dengan Simple Queue, Queue Tree, dan Hierarchical Token Bucket (Studi Kasus Pro Net Bangkinang) - Dafwen Toresa; Lisnawita Lisnawita; Fuad Renadi (Jurnal Inovtek Polbeng Seri Informatika, 2020)
Abstrack - Bandwidth management at internet service providers is something that must  implement, to avoid bandwidth struggles between clients, and to minimize the waste of available bandwidth. The method used in bandwidth management, including Simple Queue, Queue Treed and Hierarchical Tocken Bucket (HTB) In this method,  the rule will be arranged in a hierarchy consisting of parent rules and child rules. The parent rule will be the parent of all child rules below it. QoS analysis applied to Mikrotik RB951 and Ubuntu Linux based computers, then compare the results of QoS (Quality of Service) between the two devices. The author conducted QoS testing for ten days, two times in 1 day, namely the time of day and night. The best results I get are in the Queue Tree with a final score of 13, While Simple Queue, and HTB with the same value, which is 12.